Peranan Perkebunan Kelapa Sawit dalam Pembangunan Ekonomi Daerah di Kabupaten Nagan Raya - Safitri Erna; Mursidah Mursidah; Carbuna Carbuna; Aswin Nasution (Dharma Ekonomi, 2026)
Oil palm plantations constitute a leading subsector that plays a strategic role in regional economic development, particularly in Nagan Raya Regency, which is predominantly based on the agricultural sector. This study aims to analyze the role of the oil palm plantation subsector in promoting regional economic development using the Economic Base Theory as an analytical approach. A descriptive qualitative method with a literature study was employed. The data used consist of longitudinal secondary data for the period 2019–2024, sourced from official publications of Statistics Indonesia, regional development planning documents, and relevant scientific articles. The results show that the agricultural sector, dominated by the oil palm plantation subsector, makes a large and relatively stable contribution to the Gross Regional Domestic Product (GRDP) of Nagan Raya Regency, thereby qualifying it as a basic sector. This subsector also plays an important role in employment absorption, particularly in rural areas. However, the substantial economic contribution and labor absorption have not been fully accompanied by equitable improvements in community welfare, as indicated by the relatively slow decline in poverty rates. This condition suggests that the economic multiplier effect of the oil palm plantation subsector has not yet been optimal due to limited downstream activities and low value-added processing at the regional level. The study concludes that strengthening downstream industries and intersectoral linkages is necessary to ensure that the role of oil palm plantations can more effectively support inclusive and sustainable regional economic development.